2007
DOI: 10.1038/sj.leu.2404571
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of criteria for refractory cytopenia with multilineage dysplasia according to the WHO classification based on prognostic significance of morphological features in patients with refractory anemia according to the FAB classification

Abstract: In the criteria of refractory cytopenia with multilineage dysplasia (RCMD) according to the WHO (World Health Organization) classification, the frequency threshold concerning dysplasia of each lineage was defined as 10%. To predict overall survival (OS) and leukemia-free survival (LFS) for patients with refractory anemia (RA) according to the French-American-British (FAB) classification, we investigated prognostic factors based on the morphological features of 100 Japanese and 87 German FAB-RA patients, exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 11 publications
3
36
0
1
Order By: Relevance
“…We analyzed the interobserver concordance with a cutoff point of 40% dysplastic cells and found that the agreement improved in the megakaryocytic and granulocytic lineages but not in the erythroid lineage. These results agree with those of Matsuda et al 17 and Germing et al 28 who proposed raising the threshold of dysmegakaryopoiesis from 10 to 40%. The prognostic value of the WHO classification is already known.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We analyzed the interobserver concordance with a cutoff point of 40% dysplastic cells and found that the agreement improved in the megakaryocytic and granulocytic lineages but not in the erythroid lineage. These results agree with those of Matsuda et al 17 and Germing et al 28 who proposed raising the threshold of dysmegakaryopoiesis from 10 to 40%. The prognostic value of the WHO classification is already known.…”
Section: Discussionsupporting
confidence: 93%
“…We analyzed the interobserver concordance with a cutoff point of 40% dysplastic cells and found that the agreement improved in the megakaryocytic and granulocytic lineages but not in the erythroid lineage. These results agree with those of Matsuda et al 17 and Germing et al 28 who proposed raising (κ, 0.43; P<0.001). Most differences concerned the distinction of unilineage and multilineage dysplasia; consequently some patients were classified as having refractory anemia with ring sideroblasts or refractory cytopenia with multilineage dysplasia depending on the recognition of dysplasia in one or more myeloid lineages.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…At the same time it is associated with a poor prognosis of the disease. 30,31 Similarly, multiple reports continue to show that thrombocytopenia is also associated with both a worse outcome and decreased survival in MDS, 8,[32][33][34] even among low-risk MDS cases. 35 In our series, megakaryocytic dysplasia was not seen to have a significant impact on the outcome of MDS patients.…”
Section: Discussionmentioning
confidence: 98%